Size of Training Firms and Long-Run Unemployment The Role of Firms, Luck and Ability in Young Workers Careers - Renate Ingrid Neubäumer; Steffen Müller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We develop the hypotheses that the size of training firms affects long-run cumulated unemployment exposure, and that the access to large training firms depends on young workers ability and their luck to live in a region with many large and medium-sized training firms. We test these hypotheses empirically by using a large administrative data set and find corroborative evidence.
Keywords: D21; L25; L26; 330